Preliminary Safety and Efficacy of Head and Neck Cooling Therapy After Concussion in Adolescent Athletes: A Randomized Pilot Trial. Issue 4 (10th July 2022) - Congeni, Joseph; Murray, Tamara; Kline, Peyton; Bouhenni, Rachida; Morgan, Danielle; Liebig, Christopher; Lesak, Alexandria; McNinch, Neil L.
Abstract : Objective: To determine the safety and efficacy of head and neck cooling when applied up to 8 days after concussion among adolescent athletes. Design: A randomized nonblinded pilot trial. Setting: Sports Medicine Clinic in a tertiary hospital. Patients: Adolescent athletes aged 12 to 17 years diagnosed with a concussion within 1 week of injury. Interventions and Main Outcome Measures: The control group (n = 27) received standard treatment (short term brain rest), whereas the treatment group (n = 28) received standard treatment and head and neck cooling. Head and neck cooling treatment was applied to patients at the postinjury assessment visit and at 72 hours post-injury. The SCAT5 (Sport Concussion Assessment Tool) total symptom severity score was collected at postinjury assessment visit, pre- and post-treatment at 72 hours, and at 10 days, and 4 weeks post-treatment. Results: Athletes who received head and neck cooling had a faster symptom recovery ( P = 0.003) and experienced significant reduction in symptom severity scores after treatment ( P < 0.001). Sport type and gender did not influence the treatment outcome ( P = 0.447 and 0.940, respectively). Conclusions: This pilot study demonstrates feasibility of head and neck cooling for the management of acute concussion in adolescent athletes.